The role of mandatory parenting education in mitigating the impact of divorce on Muslims' children - Hasbullah @ Abdullah, Muslihah; Ramlan, Noor Yasmin; Madon, Zainal; Ahmad, Sa'odah; Juhari, Rumaya; Ahmad, Asmidah (Universiti Islam Melaka (UNIMEL), 2024)
Parental divorce poses significant risks for children that warrant concern, such as hostile conflict, the quality of parent-child relationship and the ability of parents to function effectively. Evidence-based interventions that strengthen parenting skills such as the mandatory parenting program for divorcing parents have been shown to have a positive impact on the divorced families worldwide. The possibility of Malaysia to implement similar regulation has yet to be explored. Given the rise in Muslim divorce cases, the likelihood of poor parent-child relationships following a divorce, and the fathers' noncompliance with child support orders, this study emphasizes the feasibility to create a regulatory framework for positive parenting education among divorcing parents in Malaysia. Past studies in the academic database have been examined with determined keywords. Results showed that supportive legal mechanisms that advocate for a mandatory parenting program for divorcing parents have been implemented mostly in the United States, The People’s Republic of China, Singapore and Australia. Such evidence-based programs can be divided into three broad categories which are child- focused programs, child and parent focused programs, and parent-focused programs. In most cases these programs are intended to improve outcomes for the children. Thus, the evidenced-based intervention in the form of regulatory framework for positive parenting education will contribute to support the parental divorce process when divorce is inevitable. On the other hand, it can educate the public about functional co-parenting post-divorce as the most effective ways to safeguard children’s wellbeing.